Communicative Needs in the Workplace and Curriculum Development of Business English Courses in Hong Kong. (December 2014) - Chan, Mable
The pressing need to bridge the gap between workplace communicative needs and curriculum development of business English courses has been documented in the literature. Through a questionnaire survey of 215 working adults, this study examines (a) the spoken and written needs of professionals in the local Hong Kong workplace, (b) the challenges they meet, (c) what they perceive as the most difficult spoken and written communication means, and (d) professionals' concerns about the course content to make such courses effective. This article provides insights into what constitutes an effective business English course and facilitates the teaching and learning of business English.